2004
DOI: 10.1158/0008-5472.can-03-3499
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Signal Transducer and Activator of Transcription 5 in Human Prostate Cancer Is Associated with High Histological Grade

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
189
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 162 publications
(203 citation statements)
references
References 47 publications
13
189
0
Order By: Relevance
“…Stats are a family of cytoplasmic transcription factors that can be activated (i. showed that Stat5 expression is positively related to formation of metastatic lesions (28). Although the role of Stat5 in breast tumor progression is less clear, Stat5 phosphorylation has been implicated in the pathogenesis of chronic myelogenous leukemia (29), acute myeloid leukemia (30), and prostate cancer progression (31,32). Dephosphorylation of Stat5 is believed to be mediated by protein tyrosine phosphatases (33).…”
Section: Discussionmentioning
confidence: 99%
“…Stats are a family of cytoplasmic transcription factors that can be activated (i. showed that Stat5 expression is positively related to formation of metastatic lesions (28). Although the role of Stat5 in breast tumor progression is less clear, Stat5 phosphorylation has been implicated in the pathogenesis of chronic myelogenous leukemia (29), acute myeloid leukemia (30), and prostate cancer progression (31,32). Dephosphorylation of Stat5 is believed to be mediated by protein tyrosine phosphatases (33).…”
Section: Discussionmentioning
confidence: 99%
“…40,45,57,72,78,79 Active Stat5a/b decreased both cell surface and total E-cadherin protein expression ( Figure 1A) and mRNA levels ( Figure 1B). At the same time, active Stat5a/b upregulated mesenchymal markers N-cadherin, vimentin, and fibronectin at both mRNA and protein levels in all three cell lines ( Figure 1, A and B).…”
Section: Jak2-stat5a/b Signaling Induces Expression Of Emt Markers Inmentioning
confidence: 99%
“…pcDNA-CMV-PrlR and pcDNA-CMV-WTStat5a were cloned into an adenoviral vector using BD Adeno-XTM Expression System 2 (BD Biosciences, Palo Alto, CA), as previously described, 38,41,44,45,61 and according to the manufacturer's protocol. Viral stocks of adPrlR, adWTStat5a, and adLacZ were expanded in large-scale cultures, purified by double cesium chloride gradient centrifugation, and titered side-by-side using standard plaque assay in QBI-293A cells.…”
Section: Adenoviral Generation and Gene Deliverymentioning
confidence: 99%
See 2 more Smart Citations